Rhabdomeric phototransduction initiated by the vertebrate photopigment melanopsin - Isoldi, Mauro Cesar (National Academy of Sciences, 2005)
Melanopsin is the photopigment that confers light sensitivity on intrinsically photosensitive retinal ganglion cells. Mammalian intrinsically photosensitive retinal ganglion cells are involved in the photic synchronization of circadian rhythms to the day–night cycle. Here, we report molecular components of melanopsin signaling using the cultured Xenopus dermal melanophore system. Photo-activated melanopsin is shown to initiate a phosphoinositide signaling pathway similar to that found in invertebrate photo-transduction. In melanophores, light increases the intracellular level of inositol trisphosphate and causes the dispersion of melanosomes. Inhibition of phospholipase C and protein kinase C and chelation of intracellular calcium block the effect of light on melanophores. At least four proteins, 43, 74, 90, and 134 kDa, are phosphorylated by protein kinase C upon light stimulation. This provides evidence of an invertebrate-like light-activated signaling cascade within vertebrate cells.